Ruptured Tubo-Ovarian Abscess in a Postmenopausal Woman Presenting with Septic Shock: a Case Report and Literature Review - Chun-Chieh Chi; Soon-Cen Huang (Elsevier, 2006)
Objective: To report a case of a ruptured tubo-ovarian abscess which induced septic shock in a postmenopausal woman. Case Report: A 53-year-old postmenopausal woman was transferred to our emergency department for drowsiness, hypotension, and lower abdominal discomfort. Transabdominal sonography and computed tomography showed a large pelvic tumor over the left adnexa with some ascites. The uterus and other adnexa were unremarkable. Laboratory data, including blood count and electrolytes, showed leukocytosis and azotemia. Under suspicion of a ruptured adnexal tumor, laparotomy was performed and showed a large ruptured tuboovarian tumor arising from the left adnexa with intra-abdominal pus formation. Subtotal hysterectomy and bilateral salpingo-oophorectomy led to massive bleeding during manipulation of the left adnexa because of the necrotic change in the left infundibulopelvic vessels. Deep vein thrombosis and wound disruption occurred after the operation, but, fortunately, she recovered 1 month later. Conclusion: Tubo-ovarian abscesses in postmenopausal women are uncommon but should be kept in mind with a pelvic tumor accompanied by septic shock, as this may cause a terrible outcome and other sequelae.